The Influence of Specific, Macroeconomic and ESG Factors on Banking Liquidity Risk in Indonesia - Fanu, Ridhan Azka Hani; Agustine, Elsa; Lestari, Henny Setyo (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
Liquidity risk remains a critical challenge for the banking sector, as it affects financial stability and the ability to meet short-term obligations. In Indonesia, banking liquidity is influenced by internal performance, macroeconomic conditions, and the growing emphasis on Environmental, Social, and Governance (ESG) practices. This study aims to examine the impact of bank-specific factors, macroeconomic indicators, and ESG scores on banking liquidity risk in Indonesia. Using panel data from Indonesian banks, liquidity risk is measured through two proxies: the liquid asset ratio (LC1) and the loan-to-total-assets ratio (LC2). The findings show that bank performance, represented by Net Interest Margin (NIM), positively affects LC1, while inflation has a negative impact. Bank capital and size are positively related to LC2, whereas income diversification and bank performance reduce LC2. ESG scores do not exhibit significant effects on liquidity risk. These results provide important implications for policymakers, bank managers, and researchers in designing strategies to enhance liquidity resilience and guide future studies on ESG’s role in liquidity management.